Disinformation on electoral processes in Spain: the case of the platform Elecciones Transparentes - Rodríguez-Fernández, Leticia; González-Fernández, Sara; Arce-García, Sergio (Revista Mediterránea De Comunicación, 2025)
Disinformation about electoral processes is a recurring narrative used to erode public trust in institutions and destabilize democracies. This study aims to analyze the narratives and content dissemination networks of the Elecciones Transparentes platform, an entity active since 2019 whose primary objective is to discredit electoral processes in Spain. To achieve this, a content analysis was conducted on the platform’s two websites, examining a sample of 32 videos and 10 downloadable documents. Additionally, a text mining and network theory analysis was performed on its Telegram channel, which includes all messages published from the account’s creation until January 2024, totaling 1,028 messages. This analysis also identified the platform’s connection networks and the accounts with which it shares content. The findings reveal a recurring use of simplistic narratives lacking solid arguments or data, which vary depending on the format. Audiovisual content tends to be more speculative, while textual content is more assertive. These narratives encourage citizen participation, portraying voters as watchdogs, and also impact companies and political parties.
Desinformación sobre procesos electorales en España: el caso de la plataforma Elecciones Transparentes
La desinformación sobre procesos electorales es una narrativa recurrente empleada para afectar la confianza de la opinión pública en las instituciones y dañar la estabilidad de las democracias. Este trabajo tiene como objetivo analizar las narrativas y redes de difusión de contenidos de la plataforma Elecciones Transparentes, entidad activa desde 2019, cuya finalidad es desacreditar los procesos electorales en España. Para ello, se realiza un análisis de contenido de sus dos páginas web, tomando como muestra 32 vídeos y 10 documentos descargables. Se añade un análisis de minería de textos y teoría de redes de su canal en Telegram, que recoge todos los mensajes publicados desde el origen de la cuenta hasta enero de 2024, que suponen un total de 1,028 mensajes. A través de esta observación se han identificado además sus redes de conexión, así como las cuentas con las que comparte contenidos. Entre las conclusiones se observa una repetición de narrativas simplistas, sin argumentos sólidos ni datos que tiende a variar en función del formato en el que se presenta, siendo más especulativos en los formatos audiovisuales y más incisivos en los contenidos textuales. Estas narrativas buscan que la ciudadanía asuma el papel de votante-vigilante y, además, impactan a empresas y formaciones políticas.
Keywords: disinformation; elections; electoral fraud; digital propaganda; Telegram; text mining; transparent elections; political narratives